Implementation of management of chronic disease (PROLANIS) national health insurance’s programme in community health centers in Malang - Wahyudi, Dicky Dwi; Eko Rahman Setiawan; Anggi Ardhiasti (BKM Public Health and Community Medicine, 2021)
Diabetes Mellitus and Hypertension are non-communicable diseases that have increased from year to year, both internationally and nationally. The 2018 East Java Basic Health Research Data explains that Malang City with the 4th highest Hypertension patient, following Malang Regency and Probolinggo Regency with the category of patients age ≥ 18 years. One of the benefits by National Health Insurance participants is a program that supports promotive and preventive services, namely the Chronic Disease Management Program (Prolanis) which is a National Health Insurance program for promotive and preventive services at First Level Health Facilities to overcome this diseases.Objective: To obtain an overview of implementation of the National Health Insurance Chronic Disease Management Program (Prolanis) at Malang Community Health Center. Method: In this study, data and information were collected descriptively through questionnaires filled out by Prolanis officers at 8 Puskesmas in Malang City who were randomly selected by examining Prolanis activities including: medical consultation, group education, SMS gateway reminders, and home visits. Results: Of the 8 Puskesmas studied, there was 1 community health center that did not carry out the Home visit activity. In a series of Prolanis activities (medical consultations, group education, gateway SMS reminders, and home visits) in mid-March 2020. Prolanis activities stopped due to the Covid-19 pandemic. So that Prolanis activities are carried out online via the WhatsApp group and telephone. Conclusions: Prolanis activities (medical consultation, group education, SMS gateway reminder, and home visit) at 8 Puskesmas in Malang City as a whole have been carried out in an orderly and scheduled manner, even though there are Puskesmas that do not carry out any of the home visit activities. During the Covid-19 pandemic, Puskesmas adjusted activities by making online contacts with Prolanis participants Keywords: Prolanis; JKN; Promotif; Preventif